Exploring the Role of Designated Teachers in Supporting Children and Young People in Care: An Ecosystemic Perspective - Bullingham, Robyn (2021)
Designated teachers are responsible for promoting the educational achievement and wellbeing of children and young people in care (Department for Education, 2018b). This study explored designated teachers’ perceptions around their role and the systemic factors that help and hinder their support. An ecosystemic perspective (Bronfenbrenner, 1995) was adopted throughout the data collection and analysis to examine the wider contextual factors and, in turn, provide insight into ways of strengthening their role and support for children and young people in care. This thesis drew upon qualitative methods to gain rich perspectives. Eight semi-structured interviews were conducted with designated teachers from a range of mainstream primary and secondary schools in one local authority. Data was analysed using thematic analysis in an inductive and deductive manner to allow for the integration of the Bioecological Model across themes (Bronfenbrenner, 1995). Designated teachers perceived a range of factors that supported and hindered their role across all ecosystemic levels. It is argued that the designated teacher role is strengthened by an inclusive culture, supportive ethos and shared understanding of children and young people in care across the school community, which is promoted by senior leadership. These, in turn, impacted the quality of relationships with the designated teacher. These findings are discussed with links to the previous literature base and theoretical underpinnings. The study indicates a range of possible implications for practice across the systemic levels and highlights how schools, educational psychologists and local authority services can strengthen the designated teacher role. Furthermore, the research hopes to enhance the limited research base and promote the recognition of this valuable statutory role for children and young people in care.